Diversity, distribution and dynamics of full-length Copia and Gypsy LTR retroelements in Solanum lycopersicum - Paz, Rosalia Cristina (2017)
Transposable elements are the most abundant components of plant genomes and can dramatically induce genetic changes and impact genome evolution. In the recently sequenced genome of tomato (Solanum lycopersicum), the estimated fraction of elements corresponding to retrotransposons is nearly 62%. Given that tomato is one of the most important vegetable crop cultivated and consumed worldwide, understanding retrotransposon dynamics can provide insight into its evolution and domestication processes. In this study, we performed a genome-wide in silico search of full-length LTR retroelements in the tomato nuclear genome and annotated 736 full-length Gypsy and Copia retroelements. The dispersion level across the 12 chromosomes, the diversity and tissue-specific expression of those elements were estimated. Phylogenetic analysis based on the retrotranscriptase region revealed the presence of 12 major lineages of LTR retroelements in the tomato genome. We identified 97 families, of which 77 and 20 belong to the superfamilies Copia and Gypsy, respectively. Each retroelement family was characterized according to their element size, relative frequencies and insertion time. These analyses represent a valuable resource for comparative genomics within the Solanaceae, transposon-tagging and for the design of cultivar-specific molecular markers in tomato.